Architecture, an art or a craft? Fritz Schumacher & Heinrich Tessenow - Frank, Hartmut 1942- (TU Delft Open, 2022)
This booklet contains the inaugural lectures of Fritz Schumacher and Heinrich Tessenow given on the occasion of their appointment respectively as professors at the Technical University in Dresden and The Art Academy in Dresden. The lectures provide novel insights into their understanding of architecture and into their proposals for reform of architectural education. they are proceeded by an introductory essay of the guest editor architectural historian Hartmut Frank
Keywords: Tessenow, Heinrich -- 1876-1950; Schumacher, Fritz -- 1869-1947; Architecture; Architecture / Study and teaching; Architektur; Architekturtheorie